Genetic diversity and drivers of dwarfism in extinct island emu populations. (30th April 2018) - Thomson, Vicki A.; Mitchell, Kieren J.; Eberhard, Rolan; Dortch, Joe; Austin, Jeremy J.; Cooper, Alan
Abstract : Australia's iconic emu ( Dromaius novaehollandiae novaehollandiae ) is the only living representative of its genus, but fossil evidence and reports from early European explorers suggest that three island forms (at least two of which were dwarfs) became extinct during the nineteenth century. While one of these—the King Island emu—has been found to be conspecific with Australian mainland emus, little is known about how the other two forms—Kangaroo Island and Tasmanian emus—relate to the others, or even the size of Tasmanian emus. We present a comprehensive genetic and morphological analysis of Dromaius diversity, including data from one of the few definitively genuine Tasmanian emu specimens known. Our genetic analyses suggest that all the island populations represent sub-populations of mainland D . novaehollandiae . Further, the size of island emus and those on the mainland appears to scale linearly with island size but not time since isolation, suggesting that island size—and presumably concomitant limitations on resource availability—may be a more important driver of dwarfism in island emus, though its precise contribution to emu dwarfism remains to be confirmed.